Coenzyme Q10 Stimulate Reproductive Vatality - Nie X; Dong X; Hu Y; Xu F; Hu C; Shu C (Dove Medical Press, 2023)
Xinyu Nie,1,2 Xinru Dong,1,2 Yuge Hu,1,2 Fangjun Xu,1 Cong Hu,2 Chang Shu1 1Obstetrics and Gynecology Center, First Hospital of Jilin University, Changchun, Jilin, People's Republic of China; 2Reproductive Medicine Center, Prenatal Diagnosis Center, First Hospital of Jilin University, Changchun, Jilin, People's Republic of ChinaCorrespondence: Chang Shu, Email shu_chang@jlu.edu.cnAbstract: Female infertility and pregnancy maintenance are associate with various factors, including quantity and quality of oocytes, genital inflammation, endometriosis, and other diseases. Women are even diagnosed as unexplained infertility or unexplained recurrent spontaneous abortion when failed to achieve pregnancy with current treatment, which are urgent clinical issues need to be addressed. Coenzyme Q10 (CoQ10) is a lipid-soluble electron carrier in the mitochondrial electron transport chain. It is not only essential for the mitochondria to produce energy, but also function as an antioxidant to maintain redox homeostasis in the body. Recently, the capacity of CoQ10 to reduce oxidative stress (OS), enhance mitochondrial activity, regulate gene expression and inhibit inflammatory responses, has been discovered as a novel adjuvant in male reproductive performance enhancing in both animal and human studies. Furthermore, CoQ10 is also proved to regulate immune balance, antioxidant, promote glucose and lipid metabolism. These properties will bring highlight for ovarian dysfunction reversing, ovulation ameliorating, oocyte maturation/fertilization promoting, and embryonic development optimizing. In this review, we systematically discuss the pleiotropic effects of CoQ10 in female reproductive disorders to investigate the mechanism and therapeutic potential to provide a reference in subsequent studies.Keywords: coenzyme Q10, oxidative stress, reactive oxygen species, reproductive, oocyte, endometriosis